The Port of Chancay, the Belt and Road Initiative, and Peru’s economic developmen - Lust, Jan (Geografares, 2026)
This article examines the Port of Chancay’s role in China-Peru relations, arguing that it deepens Peru’s extractivist economy and dependence. Peru is a dependent capitalist economy mainly supplying resources to advanced countries and China. While the port promises GDP growth, jobs, and logistical integration, these benefits largely exclude most people, reinforcing an exclusionary, super-exploitative model with high informality. The study highlights that Chinese investment is part of a geoeconomic strategy to secure resources, cut costs, and increase China’s influence over Peru and Latin America.